Revista Alconpat: 10 years of history (2011 - 2021) - Castro-Borges, Pedro; Sabido Maldonado , María Elizabeth; Mendoza Rangel, José Manuel; Helene, Paulo; Garcés Terradillos, Pedro; Torres-Acosta, Andrés Antonio; ,; Husni, Raúl; Troconis de Rincón, Oladis; Branco, Fernando; Escalante-García, José Iván; Alonso-Ferrera, Francisco Alberto; et al. (Revista ALCONPAT, 2021)
The objective of this work is to present to the community the achievements and challenges to come of the Alconpat Journal in its first ten years of existence. A narration is made of: how the idea of having a scientific / technical journal in Alconpat International arose; when, how and where the discussions and the project took place; the implementation, the first issue, the punctuality; the requirements and challenges to meet for the first indexations (Scielo México, Scielo WoS, Redalyc, Latindex, Google); the CONACyT projects that made it possible to gradually meet the requirements for eventual applications at higher indexes (Scopus and WoS), repositories, directories (DOAJ) and super servers; electronic markings, publication in three languages (Spanish, Portuguese and English), administrative times for publishing any specific issue, etc. At the end, an extensive acknowledgement is made to all those who have participated in these initial 10 years.